Penilaian Kinerja Perusahaan dengan Pendekatan Economic Value Added (EVA) dan Market Value Added (MVA) (Studi Kasus Pada PT Nyata Grafika Media Surakarta Periode 2012-2014 - Sardi, Evy Yulia, Dra.Chuzaimah.M.M (2016)
This study aims to identify and analyze the financial performance of companies using the approach of Economic Value Added (EVA); and Market Value Added (MVA) at PT Real Graphic Media Surakarta 2012-2014. This type of research used in this research is quantitative research. Design of this research use descriptive research design. Based on the analysis, the study concluded that: 1) Financial Performance Measurement methods Return On Assets (ROA) showed fluctuating changes. Increases and decreases in operating income is due to increased activity of the company's operations is greater than the increase in revenue generated. The amount of operating activities were financed from short-term debt resulted in net income to be received by the company no maximum; 2) Measurement of financial performance using Economic Value Added (EVA) showed an increase and decrease in the value of EVA fluctuating. It can be interpreted that the company's performance berfluktiatif and uncertain. The impairment is due to EVA NOPAT value is generated not by an increase in the value of investment costs to be borne by the Company; and 3) the weakness in weakness analysis of MVA that MVA can only be applied to companies that have gone public only. On the basis that the MVA analysis was not performed to analyze the financial statements. Graphic Media Surakarta real because the company is not a company that has gone public.